1993
DOI: 10.1126/science.262.5138.1425
|View full text |Cite
|
Sign up to set email alerts
|

Photon Emission at Molecular Resolution Induced by a Scanning Tunneling Microscope

Abstract: The tip-surface region of a scanning tunneling microscope (STM) emits light when the energy of the tunneling electrons is sufficient to excite luminescent processes. These processes provide access to dynamic aspects of the local electronic structure that are not directly amenable to conventional STM experiments. From monolayer films of carbon-60 fullerenes on gold(110) surfaces, intense emission is observed when the STM tip is placed above an individual molecule. The diameter of this emission spot associated w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
154
0

Year Published

1995
1995
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 255 publications
(157 citation statements)
references
References 22 publications
0
154
0
Order By: Relevance
“…In contrast to the conventional techniques using external light sources, scanning tunnelling luminescence (STL) spectroscopy, where luminescence is induced by the atomically localised tunnelling current of STM, provides a unique way to investigate local optical properties of matters 5,12,[14][15][16][17][18][19] . A previous STL study reports that the energy of the localised plasmon in the tunnelling junction of an STM is absorbed by molecules located close to the STM tip 20 .…”
Section: Summary Paragraphmentioning
confidence: 99%
“…In contrast to the conventional techniques using external light sources, scanning tunnelling luminescence (STL) spectroscopy, where luminescence is induced by the atomically localised tunnelling current of STM, provides a unique way to investigate local optical properties of matters 5,12,[14][15][16][17][18][19] . A previous STL study reports that the energy of the localised plasmon in the tunnelling junction of an STM is absorbed by molecules located close to the STM tip 20 .…”
Section: Summary Paragraphmentioning
confidence: 99%
“…However, experimental observations of the properties of artificial atomic scale structures created by STM have been limited until now. Gimzewski et al [4] and Berndt et al [5] have pioneered another ability of the STM. Detecting photons emitted from the tunnel gap of the STM, they showed that light emission characteristics of sample surfaces can be obtained with atomic scale spatial resolution.…”
Section: (Received 3 August 1998)mentioning
confidence: 99%
“…The STM image was recorded using normal constant current imaging conditions. Figure 1(B) shows the photon intensity as a function of the position of the STM (photon map [4,5]). The photon map was recorded at the same area as in Fig.…”
Section: (Received 3 August 1998)mentioning
confidence: 99%
“…We will focus our attention on a standard system for STM: fullerene molecules adsorbed on a metallic surface [18][19][20]. We consider a (110) oriented copper tip apex brought to the proximity of an hexagonal aggregate of seven C60 molecules adsorbed on a gold surface.…”
Section: D-field Distribution Inside the Junctionmentioning
confidence: 99%